Analisis Potensi dan Pengelolaan Desa Agro-History Wisata Menang di Kabupaten Kediri Sebagai Sarana Edukatif dan Sumber Pembelajaran IPS - Pramita Yuni; Nuansa Bayu Segara (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2022)
This article is aimed at explaining the potential and management of Agro History Menang Tourism Village in Kediri regency as well as its analysis as a means of education and social science learning resources. The Agro-History Tourism include: Agro-tourism Kampung Blimbing, Petilasan Sang Prabu Sri Aji Jayabaya, and Petirtaan Sendang Tirto Kamandanu. The research approach used is qualitative. While the type of research used is descriptive analysis. The subjects of the study were local tourist area managers, caretakers and the local community. The primary data is in the form of direct observation and participation into the field and the results of interviews with several key informants and supporters, namely tourism managers, Tourism and Culture Office of Kediri Regency, Ministry of Religious Affairs of Kediri Regency, IPS teachers and MTsN 8 Kediri learners. Data analysis is obtained through three stages, namely data reduction, data presentation, and conclusion withdrawal. The next analytical technique is to use SWOT analysis that produces a formulation of strategy analysis in utilizing the potential of Agro-History tourism in Menang Village as a means of education and source of social science learning both for the public and for related education parties. Therefore, the resulting research is the identification of the value of social knowledge contained in the potential of agro-tourism - history in Menang Village. This SWOT analysis formulation can also be used to optimize efforts to manage agro-history tourism potential in Menang Village in order to realize the natural environment and cultural history tourism that is useful and potential both in the present and in the future.